Risk assessment and anesthesia management in children with congenital heart disease undergoing non-cardiac surgery - Kemal Tolga Saracoglu; Ayten Saracoglu; Recep Demirhan (Global Journal of Anesthesiology - Peertechz Publications, 2019)
The prevalence of congenital heart disease is about 8 to 10 case per 1000 live births and is a major cause of increased mortality and morbidity in pediatric patients undergoing noncardiac surgery. Therefore safe anesthesia and adequate recovery should be provided. It is important to determine the patient's risk score in the preoperative period. However, the risk assessment tools have a limited prediction for increased mortality and morbidity of non-cardiac surgery. The most important point in determining the anesthesia method is to be aware of the latest situation both anatomically and physically about the circulation of patient and to create the specific planning. In these patients, the aim of maintenance of anesthesia is to increase arterial oxygen saturation by increasing pulmonary blood flow. Thus the use of appropriate anesthesia and monitoring methods through multidisciplinary decision-making and planning, as well as the identification of high-risk patients based on risk classification, may reduce mortality and morbidity in the pediatric patients with congenital heart disease.